PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PENINGKATAN SOFTSKILL DALAM PEMBUATAN SAMBAL TONGKOL - N.P. P. Wijayanti; E. W. Suryaningtyas; D. A.A. Pebriani; I. K.W. Negara; M. A. Pratiwi; S. A. Saraswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Klungkung Regency, Bali has highly potential of marine fisheries, especially on capture fisheries. Capture fisheries potential was estimated 4.140,7 tons per year that consist of 2.898,2 tons of pelagic fishes and 1.242,5 tons of demersal fishes. Fishery products are a source of animal protein which is very beneficial for the body because they contain high protein and low fat. Furthermore, capture fisheries products are export commodities that can contribute for foreign exchange. Handling of fresh fishes is the most important part because it can affect the quality of fish product. Handling of fishery products is generally still on a traditional scale and is managed from generation to generation with limited capacity. “Pemindangan” processing in Kusamba Village, Dawan District, is one of the fish traditional handling techniques. Kusamba Village had very high production of Frigate Tuna, however not all Frigate Tuna can be processed with Pemindangan techniques. Thus, an alternative techniques for Frigate Tuna processing is necessary to improve the value of Frigate Tuna products. This products called “Sambal Tongkol”.The advantage of Sambal Tongkol are the manufacturing process does not require a long time and special expertise so that it can be adopted by local community in Kusamba Village. In addition, Sambal is one of favorite food products for Indonesian people as a staple food companion. Sambal products have been widely developed but not many have developed with the addition of Frigate Tuna. This community empowerment activity was expected to be able to improve soft skills of coastal communities which will be able to improve their economy as well.